Audit Informasi pada Sistem Informasi Perpustakaan ITS Surabaya (SPITS): Studi Kasus Bagian Pengolahan dan Layanan di Perpustakaan ITS Surabaya - Astutik Nur Qomariyah (UIN Imam Bonjol Padang, 2019)
This study discusses the audit information in the information system of the library ITS Surabaya (SPITS). The purpose of this research is to inventory the needs and use of information on the management and the users of the library in the activities collection and processing services in hopes of providing inputs (recommended) in the the development of an integrated information system in the library of ITS Surabaya. Data collected by observation, documentation, interviews and questionnaires. Data research results were analyzed with descriptive qualitative approach through several stages of the model audit information Susan Henczel which is one of the methodology of the audit the information by applying the stages of planning, data gathering, analysis data, and the evaluation of the data. From the results of the research note that the implementation of the automated information system based SPITS used nowadays are still having some problems, which is still not providing some of the information that is required on either the management or users of the library. For it to do the audit information so that it can serve as inputs or recommendations in the plan of development of the software SPITS (the ITS Library information system) integrated